2020
DOI: 10.3390/ijms21197352
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Mechanisms of Key Nucleotides Causing Attenuation in Pathogenicity of Dahlia Isolate of Potato Spindle Tuber Viroid

Abstract: While the potato spindle tuber viroid (PSTVd) variant, PSTVd-Dahlia (PSTVd-D or PSTVd-Dwt) induces very mild symptoms in tomato cultivar ‘Rutgers’, PSTVd-Intermediate (PSTVd-I or PSTVd-Iwt) induces severe symptoms. These two variants differ by nine nucleotides, of which six mutations are located in the terminal left (TL) to the pathogenicity (P) domains. To evaluate the importance of mutations located in the TL to the P domains, ten types of point mutants were created by swapping the nucleotides between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
0
8
0
2
Order By: Relevance
“…2). 63)- 66) In particular, a C42U mutation significantly impaired PSTVd replication and did not elicit excessive host defense responses, thus contributing to the attenuation of disease symptoms. Although mutations at sites 310-312 in the VM region did not play a significant role in pathogenicity, these nucleotides, in cooperation with nucleotides 42, 43, and 64 in the paired strand, contributed to replication of the dahlia isolate by maintaining the local structure of the TL-P domains (Fig.…”
Section: Structural Motifs and Functions For Pathogenicity Of Viroid Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…2). 63)- 66) In particular, a C42U mutation significantly impaired PSTVd replication and did not elicit excessive host defense responses, thus contributing to the attenuation of disease symptoms. Although mutations at sites 310-312 in the VM region did not play a significant role in pathogenicity, these nucleotides, in cooperation with nucleotides 42, 43, and 64 in the paired strand, contributed to replication of the dahlia isolate by maintaining the local structure of the TL-P domains (Fig.…”
Section: Structural Motifs and Functions For Pathogenicity Of Viroid Rnasmentioning
confidence: 99%
“…2). 66) Bending of the molecule within the pathogenicity domain. Mutational analysis also indicated that in certain cases, downregulation of pathogenicity was correlated with suppression of the rate of PSTVd replication/accumulation.…”
Section: Structural Motifs and Functions For Pathogenicity Of Viroid Rnasmentioning
confidence: 99%
“…64 affects stunting. In general, enrichment of mutations in genomic RNAs revealed positions with importance to symptom severity and viroid replication intensity (Kitabayashi et al, 2020). The viroid genome encodes no proteins and its replication depends on the host cellular machinery.…”
Section: Pstvd Genome Structure Rna Population and Quasispeciesmentioning
confidence: 99%
“…The most frequent PSTVd genomic variants were analyzed at different time points after inoculation of tomato plants. It was found that at seven DAI only 25 % of the sequenced PSTVd genomes were identical to the master copy, but its frequency grew up to 70 % at 14 DAI and remained the same at 28 DAI (Adkar-Purushothama et al, 2020). It is likely that viroid replication produces a large variety of structural variants with different effects on host defense and the severity of disease symptoms.…”
Section: Pstvd Genome Structure Rna Population and Quasispeciesmentioning
confidence: 99%
“…Viroids are both the simplest and the smallest known plant pathogens. They consist of a circular, single-stranded, non-coding RNA genome of 246–434 nucleotides (nt) in length [ 1 ]. Since viroids do not encode for any known peptides, they rely entirely on their sequence, structure and host factors in order to replicate and induce disease symptoms in their host plants.…”
Section: Introductionmentioning
confidence: 99%